Control unit: study, compare, and discuss the recent control units - Shehadeh, ASmaa; Ghanam, Tahani; Abu Al-Jadayel, Suha (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2005)
Control unit: study , compare and discuss the most recent control units research includes an introduction to computer system in general , the research also discuss the most resent architecture RSC,CISC and superscalar machines and the characteristics for each machine. The main am for this research is to find a proper simulation that will help us to determine which architecture the best. In addition, will contain names for simulators, which help in tracing the organization of any architecture to study its performance.
Keywords: Control units